Growth Response and Cationic Uptake of Eucalytus Hybrid at Varying Levels of Soil Salinity and Sodicity - Singh, K.; Vadav, J. S. P. (Indian Forester, 1985)
performance Of Eucalyptus hybrid was evaluated under pot culture condition at artifically created varying salinity (Ecs) levels of 0.7, 4.2, 8.1, 16.3 and 22.5 m. mhos/cm and exchangeable sodium percentage (ESP) levels of 1.1, 15.2, 30.6. 61.1 and 88.7 in an alluvial satly clay laom soil by addition of different salts. Results revealed that Eucalyptus hybrid failed to grow above Ecs 16.3 m.mhos/cm and ESP 30.6. Height girth, fresh weight and dry weight of upgreded plants at the time of tremination of experiment were found to decrease with increase in Ecs or ESP. Update of Na+ by plants increased with increase in Ecs or ESP levels, while the uptake of Ca+ decreased and Mg++ and K+ did not exhibit any definite relationship with increase in salinity or acidity conditions. The values of Na/K, Na/ Ca and Na/ Mg ratios in the plant increased with increase in Ecs or ESP. Relatively lower uptake of Ca++ appeared to increase the adverse effect of sodium salts and sodic . Since the present experiments were conducted under pot culture conditions, further systematic fields studies are suggested to confirm these observations.